The Impact of Radical Love on Human Memory. (October 2020) - Racionero-Plaza, Sandra; Ugalde, Leire; Vidu, Ana; Melgar, Patricia; Navarrete, Nagore
The social impact of reading the book Radical Love cannot be grasped by the dominant discourse on the evaluation of social impact. A deep understanding of autobiographical memories must go beyond the quantitative analysis of details and episodes to qualitatively examine the meanings constructed through recollection. Thus, we explored young women's memories of intimate partner violence through memory narratives and the way these memories were reconstructed when the women read Radical Love . In addition, we examined the personal meanings given to this reading experience through in-depth interviews and a focus group. The results showed that Radical Love made the participants more critical about their memories and made these memories unappealing. This reading led some women to leave violent relationships and transform their prospective thinking. In a time when impact is measured mainly by research articles, this qualitative analysis of the memory transformation promoted by reading Radical Love demonstrates that books can also have a social impact.